Heart rate response times measured in the field as indicators for endurance performance in cycling - Knobbe, A.; Voet, J.; van Erp, T.; de Leeuw, A.-W. (Journal of Science and Cycling, 2024)
Purpose To couple power and heart rate data of professional road cyclists collected in the field and study its relationship with performance obtained in controlled settings.